Clean energy futures: An Australian based foresight study. (1st December 2022) - Gilmore, Nicholas; Koskinen, Ilpo; van Gennip, Domenique; Paget, Greta; Burr, Patrick A.; Obbard, Edward G.; Daiyan, Rahman; Sproul, Alistair; Kay, Merlinde; Lennon, Alison; Konstantinou, Georgios; Hemer, Mark; et al.
Abstract: Political decarbonisation commitments and outcompeting renewable electricity costs are disrupting energy systems. This foresight study prepares stakeholders for this dynamic, reactive change by examining visions that constitute a probable, plausible and possible component of future energy systems. Visions were extrapolated through an expert review of energy technologies and Australian case studies. 'Probable–Abundant' envisages a high penetration of solar and wind with increased value of balancing services: batteries, pumped hydro and transmission. This vision is exemplified by the South Australian grid, where variable and distributed sources lead generation. 'Plausible–Traded' envisages power and power fuel exports given hydrogen and high-voltage direct-current transmission advances, reflected by public and private sector plans to leverage rich natural resources for national and intercontinental exchanges. 'Possible–Zero' envisages the application of carbon removal and nuclear technologies in response to the escalating challenge of deep decarbonisation. The Australian critical minerals strategy signals adaptations of high-emission industries to shifting energy resource values. These visions contribute a flexible, accessible framework for diverse stakeholders to discuss uncertain energy systems changes and consider issues from new perspectives. Appraisal of preferred futures allows stakeholders to recognise observed changes as positive or negative and may lead to new planning aspirations. Highlights: Futures facilitate planning for possible outcomes rather a predicted one. Abundant: high wind/solar sees critical balancing services as in South Australia. Traded: new power/powerfuel exchanges via HVDC transmission and hydrogen. Zero: escalating decarbonisation challenges prompt nuclear and carbon removal.